: Short-term effects of exposure to particulate matter on hospital admissions for asthma and chronic obstructive pulmonary disease. Issue 35 (2nd September 2022) - Han, Chang Hoon; Pak, Haeyong; Lee, Jung Mo; Chung, Jae Ho
Abstract : We investigated the effects of particulate matter (PM) factors on hospitalization rates for asthma and chronic obstructive pulmonary disease (COPD). We obtained data on pollutants—PM10, PM2.5 —in Seoul, South Korea. We also investigated data for asthma and COPD exacerbation that required hospitalization from 2006 to 2016. We used a time-stratified case-crossover design and generalized additive models with log transformation to assess adjusted risk, and conditional logistic regression was performed to analyze these data. Our study showed that PM10 and PM2.5, on different best lag days, were associated with increased risks of COPD or asthma hospitalization. The odds ratios (ORs) for each per-unit increase in PM10 and PM2.5 were higher in patients with male asthma (PM10 : OR, 1.012; 95% confidence interval [CI], 1.008–1.016 and PM2.5 : OR, 1.015; 95% CI, 1008–1.023), preschool asthma (PM10 : OR, 1.015; 95% CI, 1.006–1.015 and PM2.5 : OR, 1.015; 95% CI, 1.009–1.024), male COPD (PM10 : OR, 1.012; 95% CI, 1.005–1.019 and PM2.5 : OR, 1.013; 95% CI, 1.000–1.026), and senior COPD (PM10 : OR, 1.016; 95% CI, 1.008–1.024 and PM2.5 : OR, 1.022; 95% CI, 1.007–1.036). Increasing PM levels increased hospitalizations for asthma and COPD. Additionally, the consequences may be different according to age and sex, and PM2.5 may have a more significant effect on airway disease patients than PM10 .